Reflexivity - de Saint Laurent, Constance; Glaveanu, Vlad (London: Palgrave Macmillan, 2016)
Do we need reflexivity in order to be creative? Many would probably be inclined to see a connection between a contemplative attitude and creativity, an image deeply rooted in our (frequently) romantic conception of the genius (Montuori & Purser, 1995). Rodin’s well-known sculpture ‘The Thinker’ embodies this association, but it also opens up the question of what the creator is actually reflecting on. Reflexivity, as commonly defined in dictionaries, suggests turning towards oneself and, in this sense, if we assume Rodin’s ‘Thinker’ is engaged in an act of reflexivity, perhaps he is deeply immersed in thought about his own condition. Is he self-absorbed? There is a crucial difference to be made between reflection and reflexivity. The old story of Narcissus tells us he was so much in love with his own image, his own reflection (in the water), that he drowned trying to reach it. Turning towards oneself, in order to foster creative action, needs, on the contrary, to create a distance between observer and observed, not collapse these two positions. Here lies the paradox of reflexivity and, at the same time, the feature that makes it essential for creativity. The observer and the observed are one and the same person and yet, to avoid self-absorption, they need to be differentiated. We can think about other people and objects in the world but, in order to reflect on oneself, the self needs to become other to itself. This accomplishment both draws on our interactions with others and defines us as social beings (Gillespie, 2006; Mead, 1934). Our definition of reflexivity is thus fundamentally social – being reflective is not a solipsistic (as in the case of Narcissus) or solitary (as in the case of Rodin’s ‘Thinker’) act. Reflexivity implies being able to take distance and look at one’s self or action from an external position. This external position can be the one of another person that we are either in dialogue with or whose views we have internalised, or even our own self as we know it from the past or imagine it in the future. All these positions facilitate de-centration, preventing us from becoming trapped in unitary, singular and egocentric views of self and world. Ultimately, such de-centration makes us flexible, creative (Gl˘aveanu & Lubart, 2014), and capable of agentic action (Martin & Gillespie, 2010). Reflexivity is important for creativity because it builds on our ability to develop new perspectives on reality, while turning these perspectives back on the self and our ongoing action. This marks the difference between creative potential (i.e., being able to generate different novel ideas) and creative achievement (i.e., using these ideas to understand things differently and act in new ways). Our argument here is that engaging in reflexivity not only generates new potential understandings of self and its situation, but prompts the person to imagine and act upon these possibilities. Through this, we are not only postulating the crucial role of others for developing a position of reflexivity, but claim that such a position is intrinsically related to (creative) action. Being reflective supports creative expression precisely because it goes beyond constructing a Narcissus-like ‘reflection’ of the self; it places multiple positions about self and world in active dialogue with each other. This dynamic is crucial for the work of artists, scientists and inventors, but it also permeates creativity in everyday life and in the social domain. The illustration that follows explores the link between creativity and reflexivity within society. It focuses on a tragic event that shook public opinion in France and internationally, occasioning unprecedented levels of social mobilisation, engaging a wide range of positions and generating a variety of (socially creative) perspectives and responses.
Keywords: Reflexivity Creativity Charlie Hebdo